PENGARUH PENGEMBANGAN SUMBER DAYA MANUSIA BERBASIS KOMPETENSI TERHADAP KINERJA ORGANISASI PADA PT. ADI LUHUNG ABADI DENPASAR - Putri Anggreni (Forum Manajemen, 2013)
PT. Adi Luhung Abadi Denpasar is representing the company which isthe in form of limited liability. PT.Adi Luhung Abadi Denpasar in itâ€™s operationalmake a move in the ï¬ eld of contactor service. This research will be analysed byinï¬‚ uence of development of human resourse (SDM) base on competence organizationperformance. In this case problem faced by PT. Adi Luhung Abadi Denpasar thatis how to manage thev existing human resourse so that earning high shownedperformance by exploiting and developing owned interest. Formulation in thisresearch problem what there isrelation and there is inï¬‚ uence of between human resourse base on the interestof to organizational performance. To get the answer of from the problems, hence will be analysed with the statistical analysis. Statisticanalysis used by is simple correlation analysis, analysed the linear regresi modestly,t-test, determination analysed and SPSS test. As for chart analysis obtained from thisresearch is showned of existence strong inï¬‚ uence and signiï¬ cation of among humanresourse base on competence to organizational performance of PT. Adi Luhung AbadiDenpasar. This matter is visible from value of correlation coeï¬ cient obtained by thatis equal to 0,743 which mean the among of development human resourse base on theorganizational performance and interest there are positive and strong link. Equationregresi obtained by that is y = 28,21 + 0,577x which mean if development humanresourse base on the interest of equal to zero, hence organizational performanceequal to 28,21 set of, and if development human resourse base on the interest increaseof equal to 1 (one) set of, hence organizational performance will mount equal to0,527 set of and so on the contrary. Result of test t-test obtained by value t-count ofequal to 6,182 bigger than value t-chart. Equal to 1,684 which reside in the area ofdeducation h0, so that hipotensis accepted which meaning there is strong inï¬‚ uenceand signiï¬ cation of among development human resourse base on the interest toorganizational performance.result analysis determination obtained by equal to55,2% what mean the organizational performance inï¬‚ uenced by development humanresourse base on the interest of equal to 55,2% and the rest of dissimilar factor iswhich is not checked.the factor for example , compensation given by a comapany,job expereince owned by each employees, cultural of job, environment of work andalso leadership style of from PT. Adi Luhung Abadi Denpasar. Thereby to can toimprove the organizational performance, hence PT. Adi Luhung Abadi Denpasarhas to improve the development human resourse base on the interest. Suggestionwhich can be raised in this research that is, company party have to be more payattention to the development human resourse. Development human resourse can beconducted to start from new employees until senior employee. Development humanresourse which can be conducted by for example on the job training, understudies, job giration, menthod demontration and follow the example of, and also menthodworker simulation.development human resourse base on the interest doesnâ€™t is onlyconducted lower management but also for the midle of management and also topmanagement.